DIEL PATTERNS OF FEEDING OF KHISBNI LIZA ABU (HEOKEL) IN RASeOIYAH RESERVOIR IN BAGHDAD, IRAQ - Islam, A K M Sirajul; Khalaf, K N (Indian Journal of Fisheries, 2011)
A single 24-hour feeding cycle of Liza abu from Rashdiyah reservoir,Baghdad, Iraq, was studied. The guts of the fish contained food almost throughoutthe period and showed two peaks — one at 0600 hours and the other at 2100hours. Organic matter and detritus formed the major bulk of the diet, followed bydiatoms, aquatic plant parts, nematodes, filamentous algae, copepods and aquaticinsects. A total of 45 species of algae belonging to 29 genera were observed inthe gut of the fish.